Patient preferences for incentives in Contingency Management interventions in methadone treatment: A best-worst scale analysis - Thuy Thi Dieu Dao; Hue Thi Nguyen; Trang Thu Nguyen; Thuyet Thi Phung; Van Hai Hoang; Huong Thi Le; Brian W. Pence; Giang Minh Le; Vivian F. Go; William C. Miller (PLoS ONE, 2026)
Background Contingency management (CM) effectively enhances adherence and retention in methadone maintenance treatment (MMT). But implementing CM in resource-limited settings is challenging, particularly due to costs associated with providing incentives. In this study, we aimed to describe and quantify patient preferences regarding low-cost CM incentives to promote adherence and retention in MMT. Methods We conducted a cross-sectional survey using a best-worst scale (case 1) among 216 participants ages 18 or older undergoing MMT in six clinics in Hanoi, Vietnam. The study asked participants to complete 13 sets of best-worst scaling tasks. Each task presented a subset of four incentives chosen from a total of 13 incentives. Net scores for each incentive were calculated by subtracting the total times an incentive was rated as least appealing from the total times it was rated as most appealing. Standardized scores were derived by dividing the net score by the sum of selections and then converted to weighted probabilities (WP) that ranged from 0% to 100% (example interpretation: an incentive with WP of 20% is twice as desired as an incentive with WP of 10%). The 95% confidence intervals (95% CI) were estimated using bootstrapping. Results The mean age of participants was 44.7 (SD = 8.0, range: 25–66). Most were male (95%), married (59%), and had not completed high school (69%). About half (50%) had been on methadone treatment for more than five years. The most preferred incentives were “discount for monthly methadone fees” (WP = 16.9, 95% CI: 16.0, 17.8) and “take-home methadone privileges” (WP = 11.3, 95% CI: 10.1, 12.6), followed by “priority coupons for early medical examinations/consultations”. In contrast, the least preferred incentives were “being recognized/praised in their community” (WP = 4.5, 95% CI: 4.0, 5.0) and “being recognized/praised at their clinic” (WP = 4.7, 95% CI: 4.1, 5.4). Conclusions Treatment fee support, take-home methadone privilege, and coupons for prioritizing checkup at clinics emerged as the most desirable incentives for patients. We recommend future CM intervention may consider using these incentives as the first-line rewards to offer to reinforce treatment adherence and retention in methadone treatment. These findings suggest potential low-cost CM strategies that could inform decision-making in MMT programs.